Marketing and Production Strategy for Impala Crackers at Dua Bebek MSME, Kandangan Village, Krembung District, Sidoarjo Regency, East Java: Strategi Pemasaran dan Produksi Kerupuk Impala Pada UMKM Dua Bebek, Desa Kandangan, Kec. Krembung, Kab. Sidoarjo, Jawa Timur - Mochammad Yusril Umam; Ika Oktaviyanti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Small and medium enterprises in the snack food sector play a vital role in local economic sustainability and community employment generation. Specific Background Kerupuk Impala Dua Bebek operates within traditional distribution networks, applying basic marketing mix strategies to maintain regional market presence. Knowledge Gap However, the transition mechanism from conventional manual distribution to digital commerce among resource-constrained food enterprises remains insufficiently explored. Aims This study analyzes product, pricing, distribution, and promotional strategies while assessing their operational impacts on enterprise competitiveness. Results Findings reveal that relying on manual marketing and additive-free production preserves product safety and local employment, but restricts shelf life and geographic market reach. Novelty This research highlights the operational trade-offs between additive-free food manufacturing and conventional distribution limitations in rural micro-enterprises. Implications Small food producers must adopt structured e-commerce strategies to mitigate competitive vulnerabilities and expand market boundaries beyond local regions. Key Findings Highlights Manual distribution and reliance on local market orders limit geographic expansion and sales growth. Manufacturing additive-free food products enhances safety but restricts shelf life and distribution range. Adopting digital platforms offers structured pathways to overcome conventional marketing constraints. Keywords: Marketing Strategy, Micro Enterprise, Traditional Distribution, Food Production, Market Reach